Analisis Yuridis Dugaan Keterlambatan Notifikasi Akuisisi Oleh Nippo Corporation Studi Kasus Putusan Perkara Nomor 16/KPPU/M/2023 - Ira Fadia Fajar; Indah Indah; Alya Rizki Asra; Wirdatul Jannah; Husnaeni Husnaeni; Septi Anisa; Siti Zulfa Masruroh; Almanda Putri Andini; Ayyesha Salsabila; Alif Nur Azis; Muhammad Qodri Hamid; Faris Hasan Aziz (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study discusses the Decision of the Business Competition Supervisory Commission (KPPU) Number 16/KPPU-M/2023 regarding the delay in notification of the takeover of PT Kadi Indonesia Manufaktur shares by Nippo Corporation. The acquisition transaction was legally effective on June 3, 2021, but was only notified to the KPPU on October 18, 2021, which exceeded the 60-day working limit according to KPPU Regulation Number 3 of 2020. The purpose of this study is to analyze the legal principles used by the KPPU and assess the application of Article 29 of Law Number 5 of 1999 in conjunction with Article 5 of Government Regulation Number 57 of 2010. The method used is normative juridical with a case study approach. The results of the study show that the KPPU applies the repressive principle, namely that legal action is taken after the violation occurs. Although no bad intentions were found on the part of Nippo Corporation, elements of violation were considered proven, including asset values ​​exceeding the threshold and negligence in fulfilling administrative obligations. As a result, KPPU imposed an administrative sanction in the form of a fine of Rp1 billion. This finding emphasizes the importance of business actors' compliance with the provisions of acquisition notifications and shows the need to strengthen socialization and preventive warnings to prevent similar violations in the future.